What Makes us Human? Maturity of the Intellect (Kamal al-‘Aql) According to al-Qadi cAbd al-Jabbar - Ibrahim, Mohd Radhi (Cultural and religious studies, 2018)
The main objective of immediate knowledge according to cAbd al-Jabbar is to prepare the ground for the person to be ready for his obligations. cAbd al-Jabbar calls this state kamal al-caql (the maturity of the intellect). When one arrives at this stage, one will be considered ready for rational obligation. cAbd al-Jabbar believes that man has an innate capacity to know the divine command that develops in him.